Long-term L-3-n-butylphthalide pretreatment attenuates ischemic brain injury in mice with permanent distal middle cerebral artery occlusion through the Nrf2 pathway - Mingying Sun; Changchun Jiang; Xiwa Hao; Jiangxia Pang; Chao Chen; Wenping Xiang; Jun Zhang; Shijun Zhao; Po Wang; Shangyong Geng; Hanzhang Wang; Yuechun Li; et al. (Heliyon, 2022)
L-3-n-butylphthalide (NBP), which is used for treatment of mild and moderate acute ischemic stroke, exerts its effects by modulating the Nrf2 pathway. However, it has not been established whether NBP exerts its preventive effects in high-risk ischemic stroke patients through the Nrf2 pathway. We investigated whether NBP exerts its preventive effects through the Nrf2 pathway in long-term NBP pretreated dMCAO mice models. Nrf2+/+ wild-type and Nrf2−/− knockout mice were randomized into the vehicle group (equal volume vegetable oil), NBP-low-dose group (20 mg/kg) and NBP-high-dose group (60 mg/kg). The drug was administered once daily by gavage for a month. Then, a permanent distal middle cerebral artery occlusion model (dMCAO) was established after pretreatment with NBP. Neurological deficits, cerebral infarct volumes, brain water contents, activities of SOD, GSH-Px and MDA levels were determined. Further, axonal injury and demyelination, expression levels of Nrf2, HO-1 and NQO1 in ischemic brains were determined. Long-term NBP pretreatment significantly improved neurological functions, reduced cerebral infarction volumes, reduced brain water contents, increased SOD, GSH-Px activities, decreased MDA contents, reduced neurological injuries, axonal damage as well as demyelination, while increasing Nrf2, HO-1 and NQO1 mRNA as well as protein expressions in dMCAO mice models.